FY 2016 Jamaica Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2017)
The Country Opinion Survey in Jamaica assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Jamaica perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Jamaica on 1) their views regarding the general environment in Jamaica; 2) their overall attitudes toward the WBG in Jamaica; 3) overall impressions of the WBG's effectiveness and results, knowledge work and activities, and communication and information sharing in Jamaica; and 4) their perceptions of the WBG's future role in Jamaica.